BACTERIOPHAGE T4 DNA-DEPENDENT in vitro SYNTHESIS OF LYSOZYME - Schweiger, Manfred (1969)
A cell-free system derived from uninfected Escherichia coli previously was shown to synthesize β-glucosyl transferase in response to T4 DNA. This same in vitro system, when incubated at slightly higher magnesium concentrations, also synthesized enzymatically active lysozyme. The lysozyme activity that appeared was judged to be T4-specific since antibodies prepared against authentic T4-lysozyme inactivated the in vitro synthesized enzyme. DNA from a T4 mutant carrying a deletion in the lysozyme gene stimulated amino acid incorporation to the same extent as wild-type T4 DNA but was inactive in directing the synthesis of lysozyme. Various inhibitors of RNA and protein synthesis inhibited the in vitro synthesis of lysozyme.